(untitled) (Cadernos de Sociomuseologia, 2025)
Museology has increasingly become a tool for critical reflection on the social, environmental, and cultural heritage preservation roles from contemporary perspectives particularly those of voices long silenced in elitist spaces. This involves the deconstruction of historical narratives through research, exhibitions, and educational activities in community museums, such as the Museum of Resistance of Boa Esperança, located in the northern zone of Teresina. Created by local community collectives to resist contemporary forms of colonization and environmental racism imposed by the urban redevelopment project Lagoas do Norte, the museum has become a space that promotes debate and fosters understanding among other marginalized groups about the power structures that continue to shape social relations, appropriate territories, and normalize social injustices. Using a methodology based on bibliographic research and recognition perspectives through the collection of oral histories and photographic records, this article objectively investigates how this community museum contributes to preserving historical memory and local narratives. It also explores how the museum engages in the fight against environmental racism and the promotion of social justice, positioning itself as a strategic tool in the struggle against both historical and contemporary inequalities. At the same time, it highlights the importance of institutions concerned with cultural issues beyond the exhibition of objects. Keywords: Museology; Environmental Racism; Museum of Resistance of Boa Esperança